Identification of Coastal Vulnerability at The North Pagai Island of Mentawai Using Smartline Method - Mutmainah, Herdiana; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Climate change and global warming have a negative impact on coastal, especially small islands. Abration and floods can be very danger and need response to minimize the disaster risks. A simple and practical method is needed to inform the location and type of coastal vulnerability and its risks along coastal segments. Smartline is a coastal management method that represents the geomorphology of coastal, hinterland and shoreline. The North Pagai is a small island, a part of the Mentawai Islands that located at the west offshore of Sumatra Island and one of the under developed areas in Indonesia. The island is surrounded by the Hindia Ocean and located on a subduction path of tectonic plate that prone to earthquakes and Tsunami. High rainfall, strong winds, the complexity of coastal morphology and also the majority of coastal residents and limited infrastructure make the problems more complicated. Tsunami in 2010 (7.7 Mw) caused the change of shoreline getting worst on The East Coast of The North Pagai Island. This study aims to identify the coastal vulnerability using Smartline method. The research was conducted on April and September 2016. The result concludes that physical aspect shows Saumangaya and Matobe Village at high and also very high level of vulnerability hence Sikakap Village at very high level. The socio-economic aspect shows that The Sikakap Village is more advanced but contrary more vulnerable to disaster in terms of population density and complex activities. The North Pagai Island is a vulnerable island from physical and socio-economic aspects.